Pengaruh Pengalaman Kerja Dan Pengembangan Karir Terhadap Prestasi Kerja Karyawan Pada PT. Remco Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2020)
ABSTRACT Â This study aims to determine the Effect of Work Experience and Career Development on Employee Job Performance at PT. Remco Palembang. This research uses quantitative research methods, with a population of 331 employees at PT. Remco Palembang. While the samples in this study were 77 employees determined using the Slovin formula this was done to facilitate data management and for better testing results. Analysis of the data used is simple linear regression analysis, multiple linear regression analysis, coefficient of determination (R2), t test and F test. The results obtained by the simple linear regression equation value of work experience Y = 7.604 + 0.618, career development Y = 12.680 + 0.493, and multiple linear regression analysis Y = 5.920 + 0.449X1 + 0.211X2. The results of the determination coefficient R2 of 0.609 or 60.90% means that work experience and career development affect work performance by 60.90%. T test results of work experience obtained a significant value of 0,000